Earnings management research: a review of contemporary research method - Sun, L.; Rath, Subhrendu (World Business Institute, 2010)
Earnings management is a much studied research topic in financial accounting. Empirical studies have documented various approaches in detecting earnings management behaviour. This study reviews various methods used in detecting earnings management and critically evaluates the strengths and weaknesses of using different methods in detecting earnings management. Although accrual approach is the most widely used technique, it has several shortcomings. We highlight these deficiencies and survey alternative methodologies that provide improvements in discretionary accruals estimation.